Competition Between Lemna minuta, Lemna minor, and Azolla filiculoides. Growing Fast or Being Steadfast? - Paolacci, Simona; Jansen, Marcel A. K.; Harrison, Simon (Frontiers in Chemistry, 2018)
A substantial number of Lemnaceae are invasive outside their natural distribution area. Lemna minuta is considered invasive in several European countries, where it can occur in the same habitat as invasive Azolla filiculoides and native Lemna minor. In this study the presence, abundance and growth rates of all three species were monitored across 24 natural ponds and in a series of mesocosms in order to explore the importance of species invasiveness and habitat invisibility. Field monitoring showed that the distribution of the three species of macrophytes is heterogeneous in space and time. However, the data show no association of nutrient or light levels with plant distribution. Indeed, using reciprocal transplanting experiments it was demonstrated that all species are able to grow in all ponds, even ponds were the species do not naturally occur. It is concluded that distribution of L. minor, L. minuta and A. filiculoides is not limited by the prevailing physicochemical characteristics of the ponds during the summer period. Remarkably, in these experiments A. filiculoides displayed the highest RGR, and exerted a negative influence on growth rates and surface cover of L. minor and L. minuta. Despite such apparent invasiveness, A. filiculoides was relatively rare in the study area. Rather, the species most abundant was L. minor which has the lowest RGR under field conditions in summer. Therefore, this study shows that the invasiveness of the species during the summer months is not necessarily reflected in the actual distribution pattern in natural ponds. In fact, alien L. minuta and A. filiculoides are under-represented in the monitored area. It is concluded that the interaction of several factors, including growth under winter-conditions and/or dispersal after disturbances, is the major determinant of the abundance and heterogeneous distribution of L. minor, L. minuta and A. filiculoides in the study area